1985
DOI: 10.1021/ac00279a038
|View full text |Cite
|
Sign up to set email alerts
|

Square-wave anodic stripping analysis in the presence of dissolved oxygen

Abstract: Substantial reductionIn analysis time has been achieved in anodic stripping analysis by eliminating the necessity lor oxygen removal. This was made possible by using square-wave voltammetry as a stripping technique in a low-pH electrolyte (0.1 M HCI04). Electroreduction of oxygen In acidic medium does not affect either the precision or the sensitivity of the method. Linear calibration plots were obtained for a model system at submicromolar concentration levels (0.1-1.3 µ Cd(II)) using short deposition times (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…It has been demonstrated that interference a) can be eliminated by combining SWASV at high frequency and background current subtraction [14,33,34]. This is applicable in sufficiently pH buffered aquatic media, such as seawater, where interference b) is weak.…”
Section: Oxygenmentioning
confidence: 99%
“…It has been demonstrated that interference a) can be eliminated by combining SWASV at high frequency and background current subtraction [14,33,34]. This is applicable in sufficiently pH buffered aquatic media, such as seawater, where interference b) is weak.…”
Section: Oxygenmentioning
confidence: 99%
“…In contrast with other voltammetric methods, the determinations can be made in the presence of dissolved oxygen when using square wave modulation [50,51]. This is particularly apparent when higher concentrations are used, as happens in SW direct methods.…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Attainment of depletive SCP conditions requires strict exclusion of oxygen (and other trace oxidants) which interfere with the straightforward relationship between I s t and c. However, deoxygenation is also required for SV measurements to avoid interference from the oxygen reduction current and the (often large) pH increases that occur at the electrode surface during deposition, especially in poorly pH buffered freshwaters [18]. Although fast scan high-frequency SW-SV can eliminate the oxygen reduction current and any interferences due to chemical oxidation of the accumulated metals [19,20], these conditions correspond to the potentially more problematic nondepletive stripping conditions described above. The same reasoning applies to claims that SCP at high stripping current is not influenced by dissolved oxygen [21].…”
Section: à3mentioning
confidence: 99%